2016
DOI: 10.1073/pnas.1518825113
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressin increases human risky cooperative behavior

Abstract: The history of humankind is an epic of cooperation, which is ubiquitous across societies and increasing in scale. Much human cooperation occurs where it is risky to cooperate for mutual benefit because successful cooperation depends on a sufficient level of cooperation by others. Here we show that arginine vasopressin (AVP), a neuropeptide that mediates complex mammalian social behaviors such as pair bonding, social recognition and aggression causally increases humans' willingness to engage in risky, mutually … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 50 publications
3
51
0
Order By: Relevance
“…Sokol-Hessner et al 2015, for example, show that propranolol, a beta-blocker, has an effect on loss aversion, but not on risk attitudes. While this is not the only study suggesting an impact of hormones on decision making (Brunnlieb et al, 2016), it does reveal that hormonal mechanisms potentially affect specific aspects of risk behavior.…”
Section: Discussionmentioning
confidence: 86%
“…Sokol-Hessner et al 2015, for example, show that propranolol, a beta-blocker, has an effect on loss aversion, but not on risk attitudes. While this is not the only study suggesting an impact of hormones on decision making (Brunnlieb et al, 2016), it does reveal that hormonal mechanisms potentially affect specific aspects of risk behavior.…”
Section: Discussionmentioning
confidence: 86%
“…Arginine vasopressin effects on human social cognition and behavior have been studied using intranasal AVP administration, which is believed to cross the blood–brain barrier ( 17 ). Most studies have been done in men, where intranasal AVP has been found to facilitate cooperation ( 18 , 19 ), enhance recognition of sexual cues ( 20 ), and enhance encoding of happy and angry faces ( 21 ). In addition, among both men and women, intranasal AVP increases empathic concern in those who received high levels of paternal warmth ( 22 ), as well as anxiety and skin conductance responses to angry faces ( 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…AVP selectively draws attention to sexual content in language ( 29 ) and increases empathic concern in both male and female subjects who had previously received high levels of warmth from their fathers ( 30 ). Intranasal AVP also facilitates cooperation in complex social decision tasks, effects that are dependent on sex, contexts of the task, and the personality of the individual ( 31 33 ).…”
Section: Introductionmentioning
confidence: 99%